Overexpression of CYP19A1 aromatase in Leydig cells is associated with steroidogenic dysfunction in subjects with Sertoli cell‐only syndrome. (21st October 2016) - Lardone, M. C.; Argandoña, F.; Flórez, M.; Parada‐Bustamante, A.; Ebensperger, M.; Palma, C.; Piottante, A.; Castro, A.
Summary: Several observational studies have showed a combination of lower testosterone (T) to LH ratio and higher estradiol (E2 ) to T ratio in secretory infertile men compared to men with normal spermatogenesis, suggesting a steroidogenic dysfunction of Leydig cells (Lc) that may involve increased aromatase activity. Low T/LH ratio is associated with Lc hyperplasia, which together with LH hyperstimulation may represent compensation for impaired T production. Aromatase expression and oestrogen production are mainly detected in Lc of the testis, although Sertoli and germ cells also contribute to testicular aromatase activity. The aim of this study was to assess the transcriptional expression of CYP19A1 (aromatase) in isolated Lc of subjects with Sertoli cell‐only syndrome (SCOS) and signs of Lc impairment. Nineteen patients with SCOS and 10 controls with normal spermatogenesis who had medical indication of testicular biopsy for sperm retrieval were studied. Leydig cells were isolated by Laser Capture Microdissection (LCM) and CYP19A1 mRNA expression was quantified by SYBR ® Green‐based qPCR. In addition, testicular T and E2 and serum hormonal levels were measured. Relative to control group, CYP19A1 was overexpressed more than twofold in 10/19 cases (2.3–12.2‐fold increase), showing a significant increment in cases with low T/LH ratio (T/LH < 2) compared to cases with T/LH ≥ 2 ( p  =   0.038, REST ® ). Moreover, Rq data for CYP19A1 had a direct correlation with testicular levels of E2 and the E2 /T ratio ( r  =   0.869; p  <   0.001 and r  =   0.633; p  =   0.005). In summary, Lc from infertile patients with signs of Lc dysfunction overexpressed aromatase and showed an increment of testicular E2 . Our results suggest that increased expression of aromatase in Lc leads to higher E2 production and may account for the functional impairment of the Lc in patients with SCOS.